Manajemen Dakwah Perwiritan Akbar dalam Meningkatkan Kualitas Ibadah Jama’ah Perempuan di Desa Klumpang Kampung - Fahzira, Khaira; Kamalia, Kamalia (Islamic Management and Empowerment Journal, 2026)
This study aims to analyze the implementation of da’wah management in Perwiritan Akbar activities and its role in improving the quality of worship among women congregants in Klumpang Kampung Village. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed descriptively to examine the application of da’wah management functions within the Perwiritan Akbar activities.The findings indicate that da’wah management has been implemented systematically through the functions of planning, organizing, actuating, and controlling. The activities include Qur’anic recitation, religious lectures, tadarus, congregational prayers, and charity programs for orphans. The implementation of these management functions contributes to improving religious understanding, consistency in worship practices, and strengthening Islamic brotherhood among women congregants.